2005
DOI: 10.1308/003588405x60713
|View full text |Cite
|
Sign up to set email alerts
|

Complications and mortality following stoma formation

Abstract: Ann R Coll Surg Engl 2005; 87: 427-431 427The annual incidence of stoma formation in England is 20,800, 1 although recent literature would suggest that this figure is unnecessarily high. The management of obstructing left-sided colorectal cancer has changed in recent times, with increased use of on -table lavage with primary resection and anastomosis 2,3 and colorectal stenting 4 to avoid stoma formation. Sphincter preserving surgery for rectal cancer should also reduce permanent stoma rates. 5Persistently hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
96
3
9

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 149 publications
(125 citation statements)
references
References 16 publications
(13 reference statements)
8
96
3
9
Order By: Relevance
“…The majority of information is incomplete or based on retrospective data analysis. This may cause under-registration of complications in most studies [5][6][7][8]. The aim of this pragmatic prospective cohort study was therefore to provide an overview of all complications that may occur after construction of an ileostomy or colostomy (loop or end) in daily practice in a large teaching hospital in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…The majority of information is incomplete or based on retrospective data analysis. This may cause under-registration of complications in most studies [5][6][7][8]. The aim of this pragmatic prospective cohort study was therefore to provide an overview of all complications that may occur after construction of an ileostomy or colostomy (loop or end) in daily practice in a large teaching hospital in the Netherlands.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, Gooszen et al 8 reported in a randomized study prolapse rates of 42% and 2% for colostomy and ileostomy, respectively. Furthermore, Harris et al 10 have recently reported a higher prolapse rate with loop colostomy as compared with ileostomy (17.4% vs 2%, P ϭ 0.001).…”
Section: Ileostomy Versus Colostomymentioning
confidence: 96%
“…However, more recent literature points to a higher prolapse rate with colostomies. 8,10 Of the colostomies, transverse loop colostomies has the highest rate of prolapse. 2…”
Section: Incidencementioning
confidence: 99%
“…Stomal prolapse, which occurs in approximately 2-22 % of patients who undergo loop colostomy, is one of the most common complications after loop colostomy [2]. A stomal prolapse is associated with an impaired quality of life.…”
mentioning
confidence: 99%